PERAN DINAS PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MENANGANI KEKERASAN TERHADAP PEREMPUAN DI KECAMATAN TELUKDALAM KABUPATEN NIAS SELATAN - Delismawati Duha (Jurnal Panah Hukum, 2023)
Victims of domestic violence are as regulated in Article 1 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is any act against a person, especially a woman that results in physical, sexual, psychological misery or suffering, and/or neglect of the house. including threats to commit acts, coercion, or unlawful deprivation of liberty within the scope of the household. To overcome domestic violence requires handling from the government through the Office of Women's Empowerment and Child Protection (DP2KBP3A), the P2KBP3A Office is one of the services in the South Nias Regency government which has the authority to assist government affairs in the field of Women Empowerment and Child Protection, in accordance with South Nias Regency Regulation Number 2 of 2021. This study uses sociological law, sociological law is a legal research method that uses empirical facts taken from human behavior, both from verbal behavior obtained from interviews and real behavior carried out through observation direct. The purpose of this study was to determine the role of the Office of Women's Empowerment and Child Protection against victims of domestic violence in South Nias Regency. The conclusion of this study is that the Office of Women's Empowerment and Child Protection has a role and assistance to victims of domestic violence, namely the role in providing psychological service assistance, referring victims to health services if needed, conducting counseling or legal socialization about preventing violence against women, Empowering women in aspects of development and potential human resources. The author suggests that the P2KBP3A Office can provide safe houses for women victims of violence